Child labour in India : globalization, power, and the politics of international children's rights - Sanghera, Gurchathen S. (Oxford University Press, 2016)
India has the largest number of child labourers in the world, and has been the subject of intense media and political campaigns in the North aimed at addressing the abuse of children's rights. This book explores these rights as a site of power and reveals how the rights discourse has been used by international actors, national elites and local NGOs in the child labour debate in India